Mahar dalam Tinjauan Hukum Islam - Parlindungan Simbolon (Al Qadhi Journal of Islamic Family Law, 2022)
The dowry is one of the conditions for a valid marriage. The obligation to give a dowry and all provisions related to marriage have been regulated in detail in Islam and have been exemplified by the prophet of Islam. What has been exemplified in Islamic sharia in the Koran and the hadith of the Prophet, not all of them can be implemented by Muslims today. Not a few Muslims who prioritize the provisions of adar in giving dowry. Giving dowry in Islam is the obligation of a husband to his wife whether paid in cash or credit based on the agreement of both parties. Dowry or dowry does not have to be with property but may be with services and teachings of the Qur'an. The dowry is fully the property of the wife and the husband may not take it unless there is permission from the wife. If the amount of the dowry is not stated in the marriage contract, then the woman is obliged to get a mitsil dowry which is the same as the dowry of women in her family. If there is a divorce before there is a husband and wife relationship, the husband is not obliged to give a dowry. However, if the husband and wife relationship has occurred, the husband must give all the dowries in accordance with the agreed amount.